Performance of purebred dairy cows and crossbred cows between Swedish Red, Swedish Holstein, Jersey, and Montbéliarde in Swedish herds - Liedgren, Sofie; Fikse, Freddy; Nilsson, Katja; Strandberg, Erling (Frontiers in Animal Science, 2024)
The use of dairy x dairy crossbreeding has increased in Sweden. This study aimed to compare crosses between Swedish Red (R), Holstein (H), Jersey (J), and Montbéliarde (M) to purebred R, H, and J for fertility, calving, production, and survival traits. The focus was on F1 crosses between either H or R on the one hand and J or M on the other hand, but also three-breed crosses were studied. There were 2,154,241 observations collected from the official cattle recording database for cows that calved between 2005 and 2020 in 7,390 herds. The dataset was separated into first and second parity and analyzed using a mixed linear model including fixed effects of breed group, herd, and year-season, and a random effect of herd-year. Fertility traits were improved in the F1 crosses with J or M compared with R or H (i.e., JR and MR vs. R; JH and MH vs. H), especially in the first parity. In parity 2, the difference was often not significant. Crossing R or H with Jersey gave lower calving difficulty than in the pure breeds in the first parity. However, crossing with Montbéliarde rather tended to give slightly more calving difficulties, albeit not significantly so. Generally, there was no significant change in stillbirths when crossing purebred R or H with J or M. There was a general tendency to better survival in the F1-crosses, however, only significantly so for Jersey crosses in parity 2 with respect to R or H. F1 between J and H (JH) had a higher 305-day fat yield than H, but lower milk and protein yields. MH had higher fat and protein yields than H and MR had higher 305d milk and protein yields than R. In conclusion, crossing R or H with either Jersey or Montbéliarde can be expected to improve fertility and probably also survival. Depending on the current situation, one could choose to improve fat yield (crossing with J) or protein yield (crossing with M), however, depending on breed, there could be a trade-off in, e.g., milk yield. For other traits, one would not expect any deterioration.